The rationale for including immune checkpoint inhibition into multimodal primary treatment concepts of head and neck cancer. Issue 1 (December 2016) - Tinhofer, Ingeborg; Budach, Volker; Jöhrens, Korinna; Keilholz, Ulrich
Abstract Background Treatment of locally advanced squamous cell carcinomas of the head and neck (SCCHN) remains unsatisfactory. Although the addition of concurrent radiochemotherapy (RCT) or the combination of radiotherapy with blockade of the epidermal growth factor receptor (EGFR) have improved outcomes over radiotherapy alone, further optimization is urgently needed. The introduction of immune checkpoint inhibitors is currently revolutionizing cancer treatment. Clinical evidence has recently been provided in melanoma that immune checkpoint blockade may cooperate with radiation. Therefore, we searched in the literature for the evidence of combining immune checkpoint inhibitors with radiotherapy in primary treatment of SCCHN. Discussion A substantial amount of previous studies has dissected the molecular mechanisms of immune evasion in SCCHN. The biological effects of radio- and chemotherapy in tumor cells and the immune cell microenvironment were characterized in detail, revealing significant interference of both types of treatment with anti-tumor immunity. This extensive review of the literature revealed considerable amount of evidence that addition of immune checkpoint inhibitors might boost the immunomodulatory potential of radiotherapy and RCT regimens in SCCHN. Summary Promising activity of immune checkpoint inhibitors has already been reported for metastatic/recurrent SCCHN. Given the immunogenic effect of radiotherapy and its enhancement by chemotherapy, combination of radiotherapy or RCT with this new type of immunotherapy might represent a valuable option for improvement of curative treatment modalities in SCCHN.